2015
DOI: 10.1007/s10600-015-1385-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Macrocyclic Conjugate of the Diterpenoid Isosteviol and Glucuronic Acid

Abstract: A macrocyclic conjugate of the natural diterpenoid isosteviol (16-oxo-ent-beyeran-19-oic acid) and glucuronic acid was synthesized for the first time. The conjugate contained two molecules of dihydroisosteviol E-D-glucuronoside joined by 1, 8-octanedicarboxylate and 1,8-octanedicarbazoyl spacers. We recently reported the synthesis of the first conjugate of the diterpenoid isosteviol (16-oxo-ent-beyeran-19-oic acid) and glucuronic acid [1] in which two molecules of the isosteviol derivative dihydroisostevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…One can see that the interaction of deprotected amino groups of glucosamine residues of diglycosides 14, 15, 18, 19 with bielectrophilic reagents will lead to their macrocyclization, and macrocyclic glycoterpenoids analogous to already known macrocycles [4][5][6][7] will be obtained. These reactions are currently being studied and will be reported soon.…”
Section: Diglycoside 14 (α-Anomermentioning
confidence: 99%
See 1 more Smart Citation
“…One can see that the interaction of deprotected amino groups of glucosamine residues of diglycosides 14, 15, 18, 19 with bielectrophilic reagents will lead to their macrocyclization, and macrocyclic glycoterpenoids analogous to already known macrocycles [4][5][6][7] will be obtained. These reactions are currently being studied and will be reported soon.…”
Section: Diglycoside 14 (α-Anomermentioning
confidence: 99%
“…Recently the first syntheses of open chain and macrocyclic glycoterpenoids having one or several diterpenoid moieties bonded with various carbohydrate residues, namely D-glucopyranose [1,2] , glucuronic acid [3][4][5] or trehalose [6,7] have been reported. In continuation of these investigations 2-deoxy-2-amino-D-glucopyranose (glucosamine) was chosen as the next carbohydrate block for macrocyclic glycoterpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It was found that these macrocycles inhibited the in vitro growth of H37Rv strain of M. Tuberculosis at the minimal inhibition concentration (MIC) value of 12.5 mg/mL that is comparable to the activity of antitubercular drug pyrazinamide. [3,4] Herein, the synthesis of the first macrocyclic glycoterpenoid having isosteviol and glucosamine residues is reported.…”
mentioning
confidence: 99%
“…[3,4] Herein, the synthesis of the first macrocyclic glycoterpenoid having isosteviol and glucosamine residues is reported. We followed the previously proposed approach [1] according to which the terminal reactive groups of binuclear isosteviol derivative are functionalized with carbohydrate residues, and these ones then are coupled by any linker. The diol 1 [4] was used as a starting compound in which two isosteviol molecules were bonded to each other with an octamethylene linker attached to their C(16) atoms, while carboxyl groups of these isosteviol moieties were functionalized by 6-hydroxyhexyl chains.…”
mentioning
confidence: 99%